(3YLGFH GdCSQGQ aj GdWdGSe hGdCOYjI hGdCPcGQs - (3eMeO Hf YHO GdhgGH Hf OGhO GdgeOGfj GdcGXej EeGe GdMQejf,J (B1305 (3g` s
(3ChdgG (B:s
(3gPg QSGdI hLjRI hLhgQI YRjRI NGdjI Yf hdfPcQ bHd GdTQhY aj GdebUhO eG jcTa Yf LdGdI Yde GdMQha s
(3BNQgG (B:s
(3hcGf WGdHkG dcTa GdGdJHGS hgh ef CTQGa GdfGS gPG Je bdJ cJGH OQN YLjH ZQjH s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B268s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(756) s
Keywords: (3GdMQha h GdChaGbs